Expression and mechanism of PRDXs family in oral squamous cell carcinoma - Zhou Zhang; Quan Zheng; Ping Li; Xiaopeng Xu; Yanzhou Zhou; Chen Qian (Discover Oncology)
Abstract Aim Our study mainly focused on exploring the expression and mechanism of PRDXs family members in OSCC, as well as the diagnostic and prognostic monitoring value of PRDXs family members in OSCC. Method We used bioinformatics tools to perform and visualize gene differential analysis on OSCC, analyse the expression of PRDXs family members in OSCC, and evaluate the diagnostic and prognostic monitoring value of PRDXs family members in OSCC patients. We utilized UALCAN, Cbioportal, and STRING websites to analyze the expression and gene mutations of the PRDXs family in pan-cancer, as well as the correlation of PRDXs family members. We used RT-qPCR technology to analyze the expression of PRDXs family members in OSCC cells. We used CCK8 technology to analyze the effect of PRDXs family members on the proliferation of OSCC cells. Result PRDX1, PRDX2, PRDX4 and PRDX5 are generally highly expressed in pan cancer, but PRDX6 is generally low expressed in pan-cancer. PRDX2 and PRDX6 have higher alteration frequency and the mutation of PRDXs family mainly focus on amplification in Pan-Cancer. PRDX1, PRDX4, and PRDX5 are highly expressed in OSCC tissue, while PRDX2 is low expressed in OSCC tissue. Similarly, PRDX1, PRDX4, and PRDX5 are also highly expressed in OSCC cells. Furthermore, PRDX1, PRDX4, and PRDX6 can promote the proliferation of OSCC cells. Except for PRDX6, all other members of the PRDXs family interact with TXN, and TXN plays a crucial role in the PRDXs family. PRDX4 has the highest diagnostic efficiency for OSCC, while PRDX2 and PRDX5 also have high diagnostic efficiency. The high expression of PRDX1 and PRDX6 suggests poor prognosis in OSCC patients, while the low expression of PRDX5 suggests poor prognosis in OSCC patients. Conclusion PRDXs family members are expressed to varying degrees in OSCC and have different diagnostic and prognostic monitoring values for OSCC, which may provide a new direction for the clinical diagnosis and treatment of OSCC patients.